1984
DOI: 10.1002/ijc.2910330215
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix components produced by SV40-transformed human epidermal keratinocytes

Abstract: The production of fibronectin, laminin and glycosaminoglycans (GAGs) has been investigated in normal and SV40-transformed human epidermal keratinocytes. Normal keratinocytes produced small amounts of laminin and fibronectin and three classes of GAGs; hyaluronic acid, heparan sulphate and chondroitin sulphate, hyaluronic acid being the major GAG. The SV40-transformed keratinocytes retained their cell-surface laminin and fibronectin, and in some cases showed elevated levels when compared to normal keratinocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
23
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…However, these cells do show certain novel quantitative changes in their ECM when compared to normal keratinocytes, the most consistent of these changes being (1) a decrease in entactin production and (2) a shift in glycosaminoglycan (GAG) production from hyaluronic acid to heparan sulphate (Brown & Parkinson, 1984;.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…However, these cells do show certain novel quantitative changes in their ECM when compared to normal keratinocytes, the most consistent of these changes being (1) a decrease in entactin production and (2) a shift in glycosaminoglycan (GAG) production from hyaluronic acid to heparan sulphate (Brown & Parkinson, 1984;.…”
mentioning
confidence: 97%
“…We have recently demonstrated that both SV40-transformed human keratinocytes and keratinocytes derived from human squamous cell carcinomas (SCCs) retain the ability to produce an extracellular matrix (ECM) (Brown & Parkinson, 1984;. However, these cells do show certain novel quantitative changes in their ECM when compared to normal keratinocytes, the most consistent of these changes being (1) a decrease in entactin production and (2) a shift in glycosaminoglycan (GAG) production from hyaluronic acid to heparan sulphate (Brown & Parkinson, 1984;.…”
mentioning
confidence: 99%
See 3 more Smart Citations